The Effects of Inattentive Responding on Construct Validity Evidence When Measuring Social–Emotional Learning Competencies. Issue 2 (7th May 2019) - Steedle, Jeffrey T.; Hong, Maxwell; Cheng, Ying
Abstract: Self‐report inventories are commonly administered to measure social‐emotional learning competencies related to college and career readiness. Inattentive responding can negatively impact the validity of interpreting individual results and the accuracy of construct validity evidence. This study applied nine methods of detecting insufficient effort responding (IER) to a social‐emotional learning assessment. Individual methods identified between 0.9% and 20.3% of respondents as potentially exhibiting IER. Removing flagged respondents from the data resulted in negligible or small improvements in criterion‐related validity, coefficient alpha, concurrent validity, and confirmatory factor analysis model‐data fit. Implications for future validity studies and the operational use of IER detection for social–emotional learning assessments are discussed.